Severe functional difficulties and disabilities in children and adolescents and the Sustainable Development Goals - Filipa De Castro; Celia Hubert; Erika Strand; Eva Prado; Ariela Braverman (Instituto Nacional de Salud Pública, 2017)
Objective. To report prevalence of severe child functional difficulties and disability (CFD) in a nationally representative sample of 2 to 17 year-old children in Mexico and describe the inequities faced by children with CFD in relation to a set of Sustainable Development Goals (SDG)-related outcomes. Materials and methods. Using data from the National Survey of Children and Women (ENIM 2015) we estimate prevalence with 95% confidence intervals for the selected indicators. We use chi-square test and confidence intervals inspection to report significant differences between children with and without CFD. Results. 8% of children present at least one CFD. CFD is associated with higher prevalence of underweight and child labor and lower prevalence of adequate early child development. Conclusion. Children with CFD present worst outcomes and require targeted efforts to ensure they meet health and wellbeing targets in the frame of the SDGs.